A 5-level multilevel inverter using LM350 voltage regulator IC - Rosnazri, Ali; Ismail, Daut, Prof. Dr.; Soib, Taib; Noor Shahida, Jamoshid (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/